The Heritage of War. - Gegner, Martin (Key issues in cultural heritage., 2011)
The Heritage of War is an interdisciplinary study of the ways in which heritage is mobilized in remembering war, and in reconstructing landscapes, political systems and identities after conflict. It examines the deeply contested nature of war heritage in a series of places and contexts, highlighting the modes by which governments, communities, and individuals claim validity for their own experiences of war, and the meanings they attach to them. From colonizing violence in South America to the United States' Civil War, the Second World War on three continents, genocide in Rwanda and continuing.